Does bank regulation matter on the relationship between competition and financial stability? Evidence from Southeast Asian countries - Noman, Abu Hanifa Md; Chan, Sok Gee; Isa, Che Ruhana (Elsevier, 2018)
This study examines the role of bank regulation on the relationship between competition and financial stability. The considered regulations are capital requirements, activity restrictions, deposit insurance, and official supervision based on prior literature. We used data from the banking sector of Southeast Asian countries over the period of 1990–2014. Using system Generalized Method of Moments (GMM) and considering financial freedom and property right as instrumental variables, this study found that competition promotes financial stability, and reduces credit risk. Further, capital requirements and official supervision are the most effective and straightforward bank regulations promoting financial stability irrespective of the level of competition. Activity restrictions are effective in shaping financial stability only in a highly competitive environment, while deposit insurance promotes financial stability in a less competitive environment. This study provides a framework to determine the bank regulation best suited to promote financial stability through the channel of competition.